An Isochore Framework Underlies Chromatin Architecture. - Kamel Jabbari; Giorgio Bernardi (PLoS ONE, 2017)
A recent investigation showed the existence of correlations between the architectural features of mammalian interphase chromosomes and the compositional properties of isochores. This result prompted us to compare maps of the Topologically Associating Domains (TADs) and of the Lamina Associated Domains (LADs) with the corresponding isochore maps of mouse and human chromosomes. This approach revealed that: 1) TADs and LADs correspond to isochores, i.e., isochores are the genomic units that underlie chromatin domains; 2) the conservation of TADs and LADs in mammalian genomes is explained by the evolutionary conservation of isochores; 3) chromatin domains corresponding to GC-poor isochores (e.g., LADs) show not only self-interactions but also intrachromosomal interactions with other domains also corresponding to GC-poor isochores even if located far away; in contrast, chromatin domains corresponding to GC-rich isochores (e.g., TADs) show more localized chromosomal interactions, many of which are inter-chromosomal. In conclusion, this investigation establishes a link between DNA sequences and chromatin architecture, explains the evolutionary conservation of TADs and LADs and provides new information on the spatial distribution of GC-poor/gene-poor and GC-rich/gene-rich chromosomal regions in the interphase nucleus.